Ošetření pankreatické pooperační píštěle gastrofistuloanastomózou - soubor kazuistik - Rudiš, J; Ryska, M (Rozhledy v chirurgii, 2012)
High incidence of postoperative pancreatic fistulas after proximal pancreatoduodenectomy has lead surgeons to search for an effective approach to treatment this life-threatening complication. There is still an absence of therapeutic guidelines in this field. The authors present 3 case reports of pancreatic fistula management with pancreaticojejunal anastomosis disconnection, retrogastric drainage and gastrofistuloanastomosis with good results.
Keywords: chirurgie trávicího traktu; Pancreaticoduodenectomy; Pancreatic Fistula; Aged; Humans; mužské pohlaví; senioři; lidé; Male; Digestive System Surgical Procedures; pankreatoduodenektomie; pankreatická píštěl